(untitled) (Bangladesh Journal of Botany, 2022)
The morpho-physiological selection and linkage between traits have been investigated. There were 20 cotton genotypes grown using RCBD with two replications at experimental area. ANOVA showed significant variation for all the traits. The GCV and PCV values of heritability and genetic advance were higher for the traits like bolls per plant, sympodial branches per plant and plant height, respectively. These traits were more under control of the genetic factors and additive gene action. There was high significant correlation between boll weight and seed cotton yield; transpiration rate and stomatal conductance. There would be yield breakthrough on considering the higher number of bolls per plant, high boll weight per plant and optimum net photosynthesis per plant as the basis of selection. Bangladesh J. Bot. 51(1): 17-22, 2022 (March)